Experimental study on improving stability of PCM and MEPCM slurry with different surfactants. (13th July 2018) - Lin, Zheng; Wei, Zhang; Shuang, Lin; Xiangyu, Jin
Abstract: Phase change materials (PCMs) are widely used in energy storage and energy transportation system as chill medium because of its large apparent heat and latent heat during phase change process. The studies on stability of PCM slurry and microencapsulation phase change materials (MEPCMs) slurry with different surfactants have been carried out in the experiments. The turbidity of the slurry was tested in order to analyze the stability of the slurry. The different surfactants polyethylene glycol400 and sodium alginate were selected to mix with PCMs' slurry. The results show that the surfactants have positive improvement effect on MEPCM slurry and negative improvement effect on PCM slurry.